2023
DOI: 10.1038/s41586-022-05500-8
|View full text |Cite
|
Sign up to set email alerts
|

River ecosystem metabolism and carbon biogeochemistry in a changing world

Abstract: Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author selfarchiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 196 publications
(115 citation statements)
references
References 164 publications
2
113
0
Order By: Relevance
“…Our synthesized estimate of global inland water CO 2 emissions would represent only about 1%–2% of continental ecosystem respiration (cf. Battin et al., 2023; Ciais et al., 2021), a proportion much lower than the uncertainties related to the quantification of this flux at global scale. However, inland water emissions are in the order of magnitude of net‐CO 2 uptake by terrestrial ecosystems (land C sink minus LUC emissions, Friedlingstein et al., 2020), and should thus be represented in detailed CO 2 budgets.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our synthesized estimate of global inland water CO 2 emissions would represent only about 1%–2% of continental ecosystem respiration (cf. Battin et al., 2023; Ciais et al., 2021), a proportion much lower than the uncertainties related to the quantification of this flux at global scale. However, inland water emissions are in the order of magnitude of net‐CO 2 uptake by terrestrial ecosystems (land C sink minus LUC emissions, Friedlingstein et al., 2020), and should thus be represented in detailed CO 2 budgets.…”
Section: Discussionmentioning
confidence: 94%
“…But also inland water CO 2 emissions, which are important in terms of GWP and total flux in the overall GHG budget of inland waters, are relatively small compared to other flux components of the continental CO 2 budget. Being mostly fed by autotrophic and heterotrophic respiration in upland soils, wetlands and aquatic systems (Abril & Borges, 2019; Battin et al., 2023), it is fair to consider inland water CO 2 emissions as a fraction of continental ecosystem respiration. Our synthesized estimate of global inland water CO 2 emissions would represent only about 1%–2% of continental ecosystem respiration (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate modeling framework to understand carbon fluxes in river ecosystems depends on the primary purpose of the model, ranging from gaining inference from specific parameters to high prediction accuracy (Currie, 2019;Rastetter, 2017;Tredennick et al, 2021). A diversity of modeling approaches that expand beyond only incorporating light and flow as the dominant controls on river metabolism (Bernhardt et al, 2022) will advance our collective understanding of the ecological processes underlying carbon fluxes in river ecosystems and how these fluxes are responding to environmental change (Battin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies currently assess inland waters net-CO 2 emissions rather as a black box that is fed by allochthonous C inputs. The recent study by Battin et al (2023) has nevertheless demonstrated that the inclusion of NEP estimates can help to disentangle autochthonous CO 2 production from allochthonous CO 2 inputs even at global scale. This study corroborates the assumption that most of the aquatic CO 2 evasion is derived from external CO 2 inputs.…”
Section: Process Understandingmentioning
confidence: 99%
“…They receive considerable amounts of reactive organic matter from terrestrial ecosystems, promoting the production of GHGs like carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O). Inland waters are usually net‐heterotrophic, meaning CO 2 production through respiration exceeds CO 2 consumption by aquatic production (Battin et al., 2023). An additional source of inland water GHG emission comes from terrestrial and wetland runoff and drainage that can be oversaturated in dissolved CO 2 produced by microbial and root respiration (Abril & Borges, 2019).…”
Section: Introductionmentioning
confidence: 99%